Operative and Technical Skills for the Senior Medical Student Entering Surgery - Mara Antonoff; Courtney Green; Jonathan D'Cunha (Association of American Medical Colleges, 2013)
Abstract Introduction Operative and technical skills focusing specifically on the basic procedures expected of surgical interns are important topics that are not uniformly covered in medical schools. We developed a course for incoming surgical interns incorporating didactics, simulation, and supervised skill practice, aimed to improve surgical intern readiness for expected procedures encountered in surgical care. Methods This resource includes comprehensive materials intended to provide senior medical students with the basic operative and technical skills to care for surgical inpatients. The materials provided were designed for use as part of a preparatory course for fourth-year medical students entering surgical specialties, and include instructor's blueprints, PowerPoint slides, and handouts for five separate sessions. A multiple-choice knowledge test is also included as one of these sessions. This resource may be used by course directors for surgery PGY-1 preparatory classes/bootcamps, for independent study by individuals planning to matriculate into surgical residencies, or as a review source for those already in surgical training. Results Learners demonstrated objective improvement in testing of cognitive skills and performance in simulated scenarios and procedures. Upon course completion, participants reported high confidence in executing skills, suggesting improved readiness for operative and technical skills necessary to care for the surgical inpatient. Discussion We feel that by significantly augmenting intern readiness, we heightened the safety and effectiveness of the medical care provided to our patients. While these materials were designed to meet the needs of new surgical house staff, the contents are easily generalizable to other medical specialties, and would prove useful for any trainee managing hospital inpatients.